Peningkatan Literasi Keuangan Siswa melalui Edukasi Pengelolaan Keuangan Pribadi di Sekolah Menengah Atas - Linda Lores; Eka Dewi Setia Tarigan; Tohap Parulian Sihombing (Universitas Pahlawan Tuanku Tambusai, 2026)
Financial literacy is an individual's ability to understand and manage finances effectively to support sound financial decision-making. Low levels of financial literacy among adolescents can influence consumer behavior and lead to an inability to manage pocket money wisely. This Community Service (PKM) activity aims to improve the financial literacy of high school students through personal financial management education. The implementation method used was interactive seminars, discussions, budgeting simulations, and evaluation using pre- and post-tests. The results of the activity showed an increase in students' understanding of personal financial management, the importance of saving, and the ability to distinguish between needs and wants. This program is expected to foster healthy financial habits from an early age in high school students.